How labor market institutions affect technological choices - Julia Samwer; Chinchih Chen (University of Hamburg, Institute of Law and Economics (ILE), 2020)
Does the adoption of technological change depend on labor market institutions? The disparities in technology adoption across countries are enormous and are a major factor in explaining poverty. The returns to introducing new technology differ across countries since they depend not only on skill-levels but also on incentives provided by labor market institutions. Wage compression through unions and minimum wage laws indirectly induce investment into technology. The employer is incenitivized to increase the productivity of employees and he can claim the full extra rent. The magnitude of the technological advancement also defines adoption rates. Small and cheaper technical changes are adopted in any institutional environment whereas larger technical progress is more likely to be integrated in rigid institutional settings. Using data on industrial robots and information and communication technology an empirical cross-country analysis explores the impact of institutional labor market patterns on technological choices and hence their influence on wage patterns, unemployment and inequality trends. It is shown that countries with strong individual labor protection adapt new technologies at higher rates, while at the same time the existence of strong unions and collective labor rights has a counter-effect.
Keywords: O33; K31; P48; 330; Technology Adoption; Labor market Institutions; Robot intensity